Harmonisasi Fungsi Non-Judicial Review Ombudsman dengan Kewenangan Judicial Review Mahkamah Agung dalam Pengujian Kebijakan Publik: Harmonizing the Ombudsman's Non-Judicial Review Function with the Supreme Court's Judicial Review Authority in Public Policy Review - Rena Zulfaidah; Tatang Astarudin (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2025)
This study analyzes the urgency of harmonizing the non-judicial review function of the Ombudsman of the Republic of Indonesia with the judicial review authority of the Supreme Court in assessing public policies. Amidst increasingly complex policy dynamics and the diversification of modern economic instruments, effective oversight mechanisms are crucial to maintaining the integrity of good governance. The core issue addressed is the overlap in perception and lack of systemic coordination, which leads to legal uncertainty for the public. Using a juridical-normative legal research method with a conceptual approach, this study evaluates the scope of authority, legal basis, and practical implications of both institutions. The results indicate that harmonization is the key to creating a comprehensive oversight system, wherein the Ombudsman addresses maladministration and sociological aspects, while the Supreme Court focuses on testing legislative norms. This synergy not only prevents oversight redundancy but also enhances legal process efficiency and national budget effectiveness. This study offers policy propositions regarding data integration and inter-institutional coordination as a solution model to ensure that every state action remains grounded in the principles of justice, transparency, and social benefit. Thus, this harmonization serves as an absolute prerequisite for building a responsive and just rule of law for all citizens in the contemporary era.